2018
DOI: 10.1007/s13399-018-0313-y
|View full text |Cite
|
Sign up to set email alerts
|

Production of volatile fatty acids from slaughterhouse blood by mixed-culture fermentation

Abstract: The volatile fatty acid (VFA) production potential from animal blood and the factors affecting this process were investigated in this study. In order to simulate an industrial process different operation modes, batch, fed batch and semi-continuous, were also evaluated. Due to high ammonia concentration in fermentation broth, VFA concentration up to 100 g L −1 was achieved without addition of buffer and methanogen inhibitor. In general, acetic, n-butyric and iso-valeric acids were the most predominant species, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…This high production is 2.5-times higher than that of VFA production (27 g VFA/L) using tuna waste from a cannery industry as raw material (Bermúdez-Penabad et al 2017) and 3.5-times higher than that of lignocellulosic material (20 g/L) and mixed food waste (20 g/L) (Forrest et al 2012;Jankowska et al 2017). To the authors knowledge, the VFA concentration achieved in this research is the second largest reported following the VFA production obtained from slaughterhouse blood (100 g/L) (Plácido and Zhang 2018b). The high VFA concentration in this process is associated with the high TAN concentration in the reactors; the advantage of using Artisanal FW is the simultaneous TAN and VFA production during hydrolysis and acidogenesis.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This high production is 2.5-times higher than that of VFA production (27 g VFA/L) using tuna waste from a cannery industry as raw material (Bermúdez-Penabad et al 2017) and 3.5-times higher than that of lignocellulosic material (20 g/L) and mixed food waste (20 g/L) (Forrest et al 2012;Jankowska et al 2017). To the authors knowledge, the VFA concentration achieved in this research is the second largest reported following the VFA production obtained from slaughterhouse blood (100 g/L) (Plácido and Zhang 2018b). The high VFA concentration in this process is associated with the high TAN concentration in the reactors; the advantage of using Artisanal FW is the simultaneous TAN and VFA production during hydrolysis and acidogenesis.…”
Section: Discussionmentioning
confidence: 61%
“…However, high protein wastes have been also effective for generating signi cant amounts of VFA. In fact, AD of Tuna FW has been able to produce approximately 30 g VFA L-1 (Bermúdez-Penabad et al 2017) and AD of slaughterhouse blood was able to produce 100 g VFA L -1 (Plácido and Zhang 2018b). Therefore, to utilise FW for VFA production and to reduce the difference between petroleum and biological based VFA production it is necessary to optimise the fermentation parameters used for this process.…”
Section: Introductionmentioning
confidence: 99%
“…The VFA concentration achieved by the artisanal FW with 2.5% concentration was higher than other FW at the same concentration, the difference in VFA production between artisanal and fish wastes is associated to the higher nitrogen concentration observed in artisanal FW than other FW reported in the literature. In other substrates, higher nitrogen concentration is associated with the production of higher amounts of VFA [35]. The production of high VFA concentrations evidence the potential of artisanal FW as raw material for the production of VFA similar to other high protein wastes such as slaughterhouse blood [35,36].…”
Section: Volatile Fatty Acids and Ammonia Production From Artisanal Fwmentioning
confidence: 98%
“…In other substrates, higher nitrogen concentration is associated with the production of higher amounts of VFA [35]. The production of high VFA concentrations evidence the potential of artisanal FW as raw material for the production of VFA similar to other high protein wastes such as slaughterhouse blood [35,36].…”
Section: Volatile Fatty Acids and Ammonia Production From Artisanal Fwmentioning
confidence: 98%
“…cause imbalance between the acidogenic and methanogenic populations, accumulation of VFA in the digester, a decline in buffer capacity, a pH decrease and the complete inhibition of the methanogenic stage [28]. The use of a high protein content feedstock can also generate an inhibitory ammonia concentration in the digester at high OLR, producing VFA concentrations as high as 100 g/L [29]. In the case of OFMSW, only thermophilic temperature can reach inhibitory ammonia concentrations [30].…”
Section: Integrated Innovative Biorefinery 51mentioning
confidence: 99%